2017
DOI: 10.15283/ijsc16032
|View full text |Cite
|
Sign up to set email alerts
|

Cavin-2 Functions as a Suppressive Regulator in TNF-induced Mesenchymal Stromal Cell Inflammation and Angiogenic Phenotypes

Abstract: Tumour necrosis factor (TNF)-α activation of mesenchymal stromal cells (MSC) enhances their tumour-suppressive properties and tumour-homing ability. The molecular actors involved are unknown. We found that TNF induced MSC migration and tubulogenesis which correlated with a dose-dependent increase in Cavin-1 and Cavin-3 transcript levels. TNF triggered cyclooxygenase (COX)-2 expression, whereas specific siRNA-mediated gene silencing of Cavin-2 resulted in an amplified COX-2 expression, tubulogenesis, and migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Codenotti et al [ 48 ] reported that CAVIN2 is a useful marker for discriminating the degree of differentiation in liposarcoma tumors. Annabi et al [ 49 ] highlighted the role of CAVIN2 in the regulation of each inflammatory and angiogenic for TNF-activated MSC. No previous reports are related to the prognosis of cancer outcomes in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Codenotti et al [ 48 ] reported that CAVIN2 is a useful marker for discriminating the degree of differentiation in liposarcoma tumors. Annabi et al [ 49 ] highlighted the role of CAVIN2 in the regulation of each inflammatory and angiogenic for TNF-activated MSC. No previous reports are related to the prognosis of cancer outcomes in patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the direct effect on ROS production, CAV1 has been proposed as a negative regulator of prostaglandin-endoperoxide synthase (PTGS) 2 (also known as COX2) [ 74 ], which can be up-regulated by ROS and mediates inflammation [ 75 ]. Interestingly, differential regulation of cavin proteins by tumour necrosis factor (TNF), a PTGS2 and inflammation inducer [ 76 ], has been observed in mesenchymal stromal cells [ 77 ]. This study also revealed a role for Cavin2 as a suppressor of TNF signalling.…”
Section: Caveolae and The Oxidative Stress Responsementioning
confidence: 99%